A stochastic parametric analysis of efficiency of millet and sorghum production in Niger - Chen, Yang (Kansas State University, 2014)
Millet and sorghum are major crops in Niger, West Africa. Improving the productivity of millet and sorghum is important to fight against poverty and malnutrition in this country. This study contributes to this objective by conducting efficiency level of millet, sorghum farmers, and the factors that influence efficiency. To reach this goal I applied a stochastic parametric frontier analysis using a cross-sectional data set collected by The Living Standards Measurement Study (LSMS) in 2011. I obtained 216 observations of plots that plant millet and 364 observations of plots that plant sorghum from 2011 to 2012 over the country. I employed Cobb–Douglas and Translog functional forms along with the half normal error distribution to estimate the production frontier. I also conducted a statistical test to choose the most appropriate functional form that fits the data for different crops. It was found that the mean technical efficiency of millet farmers is 38.44 percentage and sorghum farmers is 58.22 percentage. Lastly, I analyzed the correlates of technical inefficiency, I employed two-step approach. I found that the inefficiency of farmers is related to managerial factors such as education level or farming method.
Keywords: Millet; Sorghum production; Niger efficiency scores; Economics, Agricultural (0503)